Pembatalan Kontrak Sepihak Dalam Transaksi E-Commerce - Reza Ghovin Ankasa; Nurhasanah Nurhasanah; Ahmad Chaerul Hadi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The number of unilateral cancellations carried out by the Platform marketplace marketplace platform, which resulted in losses for consumers. The cancellation made by Platform marketplace is not without reason, but there are factors that cause the unilateral cancellation to occur. Platform marketplace then provides compensation in the form of vouchers to consumers but can only be used on the Platform marketplace platform so that consumers have limitations in using these rights. The unilateral cancellation by Platform marketplace in this study was reviewed using the Consumer Protection Act. This study aims to make consumers understand the factors that cause an order to be canceled and get accountability from Platform marketplace in accordance with the Consumer Protection Act. The method used in this research is normative research with library research type (library study) with normative juridical research methods. The main references used in the study are legislation, interviews with Platform marketplace consumers, and Platform marketplace standard agreements.